Avian Reproduction in a Warming World - Andreasson, Fredrik; Nilsson, Jan-Åke; Nord, Andreas (Frontiers in Ecology and Evolution, 2020)
Weather influences both the distribution and life-history strategies of birds. Temperature ranks amongst the more important weather parameters in this regard since warming springs in temperate and high latitudes and more frequent heat-waves globally have caused major changes in breeding phenology and negatively affected adult and juvenile survival, respectively. Both long-term and stochastic changes in temperature can have fundamental consequences for avian reproduction even when the effects are not lethal, such as via thermal constraints on parental provisioning and chick growth. To date, most of what we know about temperature effects on nestling development and parental effort during reproduction is based on correlative data. In addition, an increasing amount of evidence indicates that temperature change also significantly affects birds that breed in cooler temperate areas, which so far has been somewhat overlooked. Therefore, in this perspective piece, we outline the existing literature on temperature effects on nestling development and parental behaviour, with an emphasis on what needs to be done to address the causal effects of temperature change on avian reproduction under climate change. We finish by providing an outlook over future avenues of research, and give suggestions of some specific areas that might be especially promising in developing this field of research.